Akbar and his India - Habib Irfan (Oxford OUP, 2005)
This volume bears the imprint of a scholarship that has become unfashionable in these post-modern times. Collectively the articles provide the most authentic and representative statement on Akbar to date.
Keywords: Akbar; India-history; Mughal period